Dual-Specificity Phosphatase CDC25B Was Inhibited by Natural Product HB-21 Through Covalently Binding to the Active Site - Zhang, Shoude; Jia, Qiangqiang; Gao, Qiang; Fan, Xueru; Weng, Yuxin; Su, Zhanhai (Frontiers in Chemistry, 2018)
Cysteine 473, within the active site of the enzyme, Cdc25B, is catalytically essential for substrate activation. The most well-reported inhibitors of Cdc25 phosphatases, especially quinone-type inhibitors, function by inducing irreversible oxidation at this active site of cysteine. Here, we identified a natural product, HB-21, having a sesquiterpene lactone skeleton that could irreversibly bind to cys473 through the formation of a covalent bond. This compound inhibited recombinant human Cdc25B phosphatase with an IC50 value of 24.25 μM. Molecular modeling predicted that HB-21 not only covalently binds to cys473 of Cdc25B but also forms six hydrogen bonds with residues at the active site. Moreover, HB-21 can dephosphorylate cyclin-dependent kinase (CDK1), the natural substrate of Cdc25b, and inhibit cell cycle progression. In summary, HB-21 is a new type of Cdc25B inhibitor with a novel molecular mechanism.